2013
DOI: 10.4049/jimmunol.1201965
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Gammaglobulin Inhibits Encephalitogenic Potential of Pathogenic T Cells and Interferes with their Trafficking to the Central Nervous System, Implicating Sphingosine-1 Phosphate Receptor 1–Mammalian Target of Rapamycin Axis

Abstract: Despite an increasing use of high-dose therapy of i.v. gammaglobulin (IVIg) in the treatment of various T cell– and Ab-mediated inflammatory and autoimmune diseases, comprehension of the mechanisms underlying its therapeutic benefit has remained a major challenge. Particularly, the effect of IVIg in T cell–mediated autoimmune conditions remains unexplored. Using an actively induced experimental autoimmune encephalomyelitis model, a T cell–mediated autoimmune condition, we demonstrate that IVIg inhibits the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
7
48
1
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26] However, the cellular and molecular mechanisms by which IVIg expands Tregs are relatively unknown. As Treg expansion in the periphery requires signaling by antigen-presenting cells such as dendritic cells (DCs) 27,28 and IVIg has been demonstrated to modulate DC functions, [29][30][31][32] we hypothesized that IVIg induces distinct signaling events in DCs.…”
Section: Foxp3mentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20][21][22][23][24][25][26] However, the cellular and molecular mechanisms by which IVIg expands Tregs are relatively unknown. As Treg expansion in the periphery requires signaling by antigen-presenting cells such as dendritic cells (DCs) 27,28 and IVIg has been demonstrated to modulate DC functions, [29][30][31][32] we hypothesized that IVIg induces distinct signaling events in DCs.…”
Section: Foxp3mentioning
confidence: 99%
“…EAE was induced in 10-weekold female C57BL/6J mice (Janvier, Saint Berthevin, France) and evolution of disease was followed as previously reported. 15,26 EAE was induced in 3 different groups and each group included 6 to 8 mice. Mice were immunized with 200 mg of MOG peptide (MEVGWYRSPFSRVVHLYRNGK; PolyPeptide laboratory, Strasbourg, France) emulsified in complete Freund's adjuvant (Sigma-Aldrich) containing 880 mg of nonviable Mycobacterium tuberculosis H37RA.…”
Section: Eae Model and Treatment With Ivig And Ns-398mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was demonstrated that polyclonal IgG inhibits the in vitro proliferation of human T cell lines reactive against myelin basic protein (MBP) [42]. As recently shown, it may impede lymph node egression of encephalitogenic T cells by downregulation of sphingosine-1-phosphate receptor 1 [43]. Furthermore, polyclonal IgG may inhibit T cell migration across the blood-nerve barrier [44,45].…”
Section: Reviewmentioning
confidence: 96%
“…[51][52][53][54][55][56][57][58][59][60]. To date, IVIGs' beneficial effects areTable 1Selected mechanisms of action of IVIG in human disease and experimental models of autoimmune diseases (reviewed by[55])…”
mentioning
confidence: 99%